Does Brand Love Make Every Consumer Behave On Social Media ? The Role of Personality Traits and Brand Love On Customer Engagement Behavior - Dwi Martiyanti (AMAR (Andalas Management Review), 2022)
The customer engagement behavior is an important concept for the company along with the increasing use of social media by consumers. Previous studies examined customer engagement behavior on social media by the role of technology factors or features on the brand page. Nevertheless, the role of individual consumer traits and the consumer-brand relationships on customer engagement in brands on social media are still limited. This paper aims to explore customer engagement behaviours to brands in social media. This explores the extent to which personality traits are related to consumer-brand relationship and customer engagement behaviours in social media. The findings are presented from a survey of Instagram users who engage with fashion brand pages. The data collecting was done by online survey from 209 respondents, age between 18 and 34 years. The results support four of the seven hypotheses with significant relationship between the constructs analysed. Customers with openness and extraversion tend to love brands. Openness performs engagement behavior to brands in Instagram but extraversion does not. On the other hand, individuals who have neuroticism tend not to love brands and not perform engagement behavior. Eventually, brand love is a strong customer motivation to perform customer engagement. This study contributes to existing literature by examining consumer behavior on social media in the presence of emotional motivation. This paper extends literature by studying combined effect of emotional motivation resulting from the presence of personality traits in individual customer behavior